BRAND NAMES FROM TWO ANTHROPONOMY - S. M. Akhmadalieva (Web of Journals Publishing, 2024)
The article discusses brand names that are formed by combining two anthroponyms.
Keywords: Brand name, anthroponym + type of activity, anthroponym + adjective, linguacultural task.